Optimization of the power–transportation coupled power distribution network based on stochastic user equilibrium - Ma, Xiping; Jin, Yanpeng; Li, Jinju; Zhen, Wenxi; Xu, Rui; Cao, Ge (Frontiers in Energy Research, 2024)
With the increasing penetration of electric vehicles in road traffic, the spatial and temporal stochasticity of the travel pattern and charging demand of EVs as a mode of transportation and an electrical load has generated different degrees of congestion impacts on both the power grid and the transportation network. Based on this, this paper proposes a power-transportation coupling distribution network optimization strategy based on stochastic user traffic equilibrium theory. Firstly, a stochastic user equilibrium mixed traffic flow allocation model that expresses users' non-completely rational path selection behavior is established, and the traffic flow equilibrium solution is obtained by solving using an improved Method of Successive Algorithm and mapped to charging loads. Second, a distribution network power flow optimization model under the coupled power-transportation architecture is established to optimize the operation state of the distribution network by combining distributed resources such as energy storage, demand response loads, wind power, photovoltaic, and gas turbines.